Longitudinal trends in the prevalence and treatment of depression among adults with cardiovascular disease: An analysis of national health and nutrition examination survey 2009–2020 - Feng, Zhen; Tong, Wai Kei; Tang, Zhijia (Frontiers in Psychiatry, 2022)
Objective: To assess the contemporary prevalence and decadal trends of depression and antidepressant use among adults with cardiovascular disease (CVD) in the United States, as well as their risk factors from 2009 to 2020. Methods: We used the National Health and Nutrition Examination Survey data to calculate the weighted prevalence of depression and antidepressant use. Adults aged 20 years or older with CVD were included. Depression and CVD were assessed by the Patient Health Questionnaire (PHQ-9) and self-report, respectively. Results: A total of 3,073 eligible participants with CVD aged >20 years were included. The overall prevalence of depression defined by PHQ-9 score ≥10 was 15.7% (95% CI 13.8-17.5), with a steady trend during 2009-March 2020 (p=0.777). Female gender (aOR 1.78, 95% CI 1.20-2.64) and sleep disorder (aOR 2.62, 95% CI 1.78-3.86) were independent risk factors for depression in CVD patients, while high education level, high income, longer sleep duration, and non-current smokers were considered protective factors. The weighted prevalence of antidepressant use among depressed patients with CVD was 38.6%, which also remained unchanged during the survey period (p=0.699). Participants with normal sleep pattern and duration were significantly less likely to take antidepressants (p=0.003). Conclusions: The longitudinal trends in the prevalence of depression among CVD patients in the United States have been stable over the past decade, despite being significantly higher in women, and those with sleep disorders. Overall, antidepressant use was fairly low. Aggressive screening and tailored treatment are recommended for specific vulnerable subpopulations to improve their clinical outcomes.